Electrocardiogram Monitoring Practices for Hospitalized Adults Receiving Antipsychotics: A Retrospective Cohort Study. Issue 2 (March 2022) - Sinvani, Liron; Afroz-Hossain, Anika; Muran, Andrew; Strunk, Andrew; Williams, Myia S.; Qiu, Michael; Zeltser, Roman; Makaryus, Amgad N.; Wolf-Klein, Gisele; Pekmezaris, Renee
Abstract : Objective: Antipsychotics are frequently used for managing both acute and chronic neuropsychiatric disorders. While antipsychotics are known to be associated with increased mortality due to cardiac arrhythmia, there is a lack of consensus on the timing and frequency of electrocardiogram (ECG) monitoring.  The goal of this study was to examine current ECG monitoring practices for adults receiving antipsychotics, specifically during hospital admission. Methods: The study involved a multisite retrospective chart review of adults admitted across 8 hospitals between January 2010 and December 2015 who received antipsychotics during hospitalization. The primary outcome was the presence of an ECG after receiving an antipsychotic. Results: During the study period, there were 26, 353 hospitalizations during which adults received antipsychotic medication; the average age of the patients was 61.4 years, 50.1% were female, and 64.8% were white. The average comorbidity score was 1.4 with a median length of stay of 8.3 days. Of the 26, 353 patients who were hospitalized, 60.6% (n=15, 977) of patients in the sample had an ECG during their hospitalization, and 41.2% (n=10, 865) had the ECG following antipsychotic administration. Patients who received a follow-up ECG had a longer length of stay (median: 11.3 d) compared with those who did not receive a follow-up ECG (median: 7.0 d). Follow-up ECGs were more likely among patients who had a history of heart failure [odds ratio (OR)=1.17, 95% confidence interval (CI): 1.06-1.30, P =0.002], who were receiving multiple antipsychotics (OR=1.3, 95% CI: 1.24-1.36, P <0.001) or other QT-prolonging medications (OR=1.09, 95% CI: 1.07-1.1, P <0.001), who were receiving risperidone (OR=1.12, 95% CI: 1.004-1.25, P =0.04), and who showed an increase in QTc duration (OR per 10 ms increase=1.02, 95% CI: 1.01-1.04, P =0.003). Follow-up ECGs were less likely to be administered to patients who were receiving antipsychotics before admission (OR=0.93, 95% CI: 0.87-0.997, P =0.04). Conclusions: This study demonstrated that, in a large health system, ECG monitoring is not routinely practiced for hospitalized patients receiving antipsychotics. Further studies are needed to identify patients who would most benefit from ECG monitoring in the acute care setting.